Occupational injuries, mental workload and coping strategies among the nursing workforce in the Eastern Region of Ghana: a multi-centre study - Collins Atta Poku; Abital Ayergo Ahulu; Janet Otomo; Doris Hagan; Catherine Kroamah Dwumfour; Joseph Shahadu Issifu; Veronica Dzomeku (BMC Nursing)
Abstract Background The nursing profession plays a crucial role in the quality of healthcare services. While nurses face occupational injury challenges globally, mental workload, which is often overlooked, plays a significant role in these injuries. Understanding nurses’ coping strategies can help develop effective interventions. The study examined the influence of mental workload on occupational injuries and coping strategies among nurses. Methods A multi-centre cross-sectional study was conducted in selected hospitals in the Eastern Region of Ghana. Using a stratified sampling technique, 317 nursing staff from 6 hospitals participated in the study. A researcher-developed occupational injury questionnaire, NASA Task Load Index and Brief COPE scale were used to measure occupational injury, mental workload and coping strategies among nurses. Descriptive statistics, Pearson moment-product correlations, and regression analysis were used to analyse the data at a statistical significance of 0.05. Results Needle pricks, injuries from sharps, exposure to blood and other body fluids, and back pain and injury from patient handling tasks were shared among participants in the past year. The study also revealed a high level of mental workload among participants. A significant correlation was observed between mental workload and various occupational injuries. The participants adopted different coping strategies in dealing with the mental workload, with active coping and instrumental support being the most used coping strategies. Conclusion The findings underscore the importance of addressing mental workload in nursing to reduce occupational injuries. To achieve this, nurses must be provided with appropriate coping strategies and support to minimise mental stress. Implication Providing accessible and effective coping strategies tailored to nurses’ needs can significantly improve their well-being and job performance. Healthcare administrators and policymakers should consider these results when designing interventions to support the nursing workforce.